(68)Ga-DOTATATE PET/CT Compared with (131)I-MIBG SPECT/CT in the Evaluation of Neural Crest Tumors - Shahrokhi, Pezhman (Asia Ocean J Nucl Med Biol, 2020)
OBJECTIVE(S): (68)Ga-DOTATATE positron emission tomography (PET)/computed tomography (CT) has shown promising results in imaging of neural crest tumors (NCT). Herein, we compared the performance of (68)Ga-DOTATATE PET/CT and (131)I-MIBG single photon emission computed tomography (SPECT)/CT in the initial diagnosis, staging and follow-up of patients with NCTs. METHODS: Twenty-five patients (males:females=8:17; age range=2–71 years) with clinically proven or suspicious neuroblastoma, pheochromocytoma (PCC) or paraganglioma (PGL) were enrolled in this prospective study and underwent both (68)Ga-DOTATATE PET/CT and (131)I-MIBG SPECT/CT. A composite reference standard derived from histopathological information, together with anatomical and functional imaging findings, was used to validate the results. Imaging findings were assessed on a per-patient and on a per-lesion basis. Sensitivity and accuracy were assessed using McNemar’s test. RESULTS: Referring to radiological imaging and histopathological findings as reference standard, (68)Ga-DOTATATE and (131)I-MIBG scans showed a sensitivity and accuracy of (100%, 96%) and (86.7%, 88%), respectively, on a per-patient basis. In PCC/PGL patients, on a per-patient basis, the sensitivity of (68)Ga-DOTATATE was 100% and that of (131)I-MIBG was 77.8%. In neuroblastoma patients, on a per-patient basis, the sensitivities of both (68)Ga-DOTATATE and (131)I-MIBG were 100%. Overall, in this patient cohort, (68)Ga-DOTATATE PET/CT identified 52 lesions and (131)I-MIBG SPECT/CT identified only 30 lesions. On a per-lesion analysis, (68)Ga-DOTATATE was found to be superior to (131)I-MIBG in detecting lesions in all anatomical locations, particularly osseous lesions. According to the McNemar test results, differences were not statistically significant. CONCLUSION: This relatively small patient cohort suggests (68)Ga-DOTATATE PET/CT be superior to (131)I-MIBG SPECT/CT in providing particularly valuable information for both primary staging and follow-up in patients with NCT.